Unidentified Aerial Phenomena: The VASP-169 Flight Brazilian Episode Revisited - da Silva, Luiz Augusto (Journal of Scientific Exploration, 2014)
The February 8, 1982, sighting of an unidentified aerial phenomenon by crew and passengers in the VASP-169 flight over Brazil had significant media repercussions at the time and is still referred to today by several UFO publications. In this paper we reinvestigate the occurrence in depth and suggest that the "object" was indeed the planet Venus, possibly distorted by an atmospheric mirage effect. An almost simultaneously occurring but lesser-known secondary case is also commented upon. Keywords: UFOs-VASP 169 Brazilian case-planet Venus-mirages